Pengaruh Pembelajaran Jarak Jauh Terhadap Perkembangan Remaja Usia 15-19 Tahun di SMA Negeri 1 Cariu - Sri Seven Yarnitien Zalukhu; Ayu Sutrisna; Napoleon Manalu (Jurnal Silih Asah, 2024)
This thesis is the result of research that shows the extent of the influence of Distance Learning on the development of adolescents aged 15-19 years. One of the impacts of the covid 19 pandemic is that learning is carried out remotely in accordance with government policies in the Ministry of Education and culture Circular Number 15 of 2020. The learning system implemented was influential for the development of adolescents. The purpose of this study was specifically to determine the extent of the influence of Distance Learning on the development of adolescents aged 15-19 years in SMA Negeri 1 Cariu, Bogor, West Java. The research methods used are quantitative methods with data collection techniques used are observation, interviews, literature studies and questionnaires. The location of the study at SMA Negeri 1 Cariu which is located at Jl. Transyogi, RT.17/RW.06, Cariu, District. Cariu, Bogor regency, West Java 16840, with a population of 950 and a sample of 95 respondents. Data analysis and data processing techniques using Ms. Excel 2010 and SPSS 25 for Windows. The results showed that the influence of distance learning on the development of adolescents 15-19 years in SMA Negeri 1 Cariu amounted to 97.5% and other presentations are influenced by other factors. Based on the results of the analysis and conclusions in the discussion chapter, the researchers provide and propose suggestions or input as follows: First, the counseling teachers of SMA Negeri 1 Cariu, are constantly involved in improving counseling for learners in order to supervise and control every aspect of development. Second, all elements related to lecturers, teachers, and parents can promote more intense and open communication.